Rural education and rural realities: the politics and possibilities of rural research in southern Africa - Balfour, Robert J.; De Lange, Naydene; Khau, 'Mathabo (Faculty of Education, University of the Free State, 2012)
Abstract not available
Keywords: Rural research; Rural education; Rural life in southern Africa